The effect of organizational culture, career development remuneration and job satisfaction on nurse performance in regional general hospital in batam embung fatimah city - Nelli Roza; Yetty Supriyati; Kadir (IJHCM (International Journal of Human Capital Management), 2022)
Hospitals are obliged to provide safe, quality, anti-discriminatory, and effective health services by prioritizing the interests of patients in accordance with hospital service standards. For this reason, hospitals are required to provide professional health workers, one of which is a nurse. Conditions in the field there are still many patient complaints about hospital services. To answer this problem, it is necessary to evaluate the performance of nurses in hospitals and see the factors that influence it. The purpose of this study is to develop a model which states that nurse performance is mediated by job satisfaction which is supported by organizational culture, career development and remuneration which also pays attention to the relationship between career development variables and remuneration. This research was conducted at the Embung Fatimah Regional General Hospital, Batam City using a survey method and involving 200 clinical nurses as respondents. Data were collected using a Likert scale with Construct Reliability (CR) 0.70 and Variance Extrated (VE) 0.50. Data were analyzed using Structural Equation Modeling (SEM) with LISREL 8.8 and SPSS software. The research findings for the measurement model reveal that all variables have SFL > 0.50 which indicates that all variables are valid. Likewise for the reliability of consistently measuring all indicators of research variables, it can be concluded that the reliability of the measurement model of all latent variables is good. Furthermore, the findings of the structural model reveal that organizational culture, career development, remuneration and job satisfaction have a direct positive effect on nurse performance. In addition, there was also a positive direct effect of career development and remuneration on job satisfaction, and the dominant direct influence of career development on remuneration (t-value = 12.01 > 1.96), but there was no direct positive effect of organizational culture on job satisfaction ( t-value = 1.47 < .96). The conclusion of this study, is to improve the performance of nurses at the Embung Fatimah Regional General Hospital, Batam more effectively through improving remuneration management, and implementing career development in accordance with applicable regulations compared to organizational culture.